Establishing the Genotyping of NPHS2 Polymorphisms in Patients with Primary Nephrotic Syndrome - Nhung, Pham Thi Hong; Nga, Vu Van; Linh, Nguyen Thi Thuy; Hoanh, Do The; Dem, Pham Van; Long, Dinh Doan; Thom, Vu Thi (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 33 No 2DO - 10.25073/2588-1132/vnumps.4066, 2017)
Podocin protein is encoded by the NPHS2 gene is largely responsible for resistance to corticosteroid in pharmacological treatment of nephrotic syndrome. Therefore, we have constructed the genotyping test of NPHS2 polymorphisms on 149 pediatric patients with primary nephrotic syndrome. Main methods consisted of DNA extraction from peripheral blood samples, polymerase chain reaction (PCR) and Sanger sequencing. In my study, 251 SNPs from 6 exons and 2 new mutations have detected by genotyping test. These results will provide helpful tool and data for further research to determine the role of NPHS2 polymorphisms with corticosteroid response in the treatment of nephrotic syndrome.